LNG-Based Decarbonization of Small-Scale Maritime Transport: A Technical and Economic Feasibility Study in North Kalimantan - Henny Pasandang Nari; Yong Wong Kim; Mahadir Sirman; Romy Sumardiawan (Journal of Renewable Energy and Smart Device, 2026)
Indonesia's vast natural gas reserves present a strategic opportunity to decarbonise its maritime sector, particularly in archipelagic regions such as North Kalimantan, where small wooden and fiberglass vessels rely on high-cost, high-emission diesel fuels, posing environmental and economic challenges. This study employed a mixed-methods approach, combining fuel consumption simulations with stakeholder surveys and interviews to evaluate the technical, economic, and policy feasibility of adopting liquefied natural gas (LNG) for non-conventional inter-island vessels. The technical analysis compared LNG and biodiesel performance on a Mitsubishi 89 kW marine engine regarding thermal efficiency, specific fuel consumption (SFC), and operational costs. Simulation results show that LNG-powered engines achieved 46.46% thermal efficiency and an SFC of 0.140 kg/kWh, compared to 33.85% and 0.1847 kg/kWh for biodiesel. An economic feasibility analysis across eight inter-island routes demonstrated fuel cost savings of 51–68% with LNG relative to biodiesel, with an estimated simple payback period of 3.2–4.5 years for dual-fuel engine retrofitting under baseline fuel price assumptions. Stakeholders acknowledged LNG's benefits but raised concerns about infrastructure limitations and regulatory readiness. This study concludes that LNG adoption for non-conventional vessels is economically and environmentally viable, particularly when aligned with Indonesia's broader energy transition strategies, and provides a scalable model for other archipelagic maritime regions seeking to reduce emissions and fuel dependency.